The role of polyphenols in the prevention and treatment of cancer - Szypuła, Aleksandra; Michalik, Beniamin; Galasińska, Iwona; Hajduk-Maślak, Katarzyna; Skóra, Adrianna; Sęk, Michał (Journal of Education, Health and Sport, 2024)
Introduction: Polyphenolic compounds are widespread in nature, contained in large quantities especially in fruits, vegetables, cereals and nuts. In recent years numerous attempts have been made to characterize their biological effects, with particular emphasis on their protective potential against the development of chronic diseases, including cancer. Purpose of the study: The aim of the study was to collect and analyze publications on the use of polyphenols in the prevention and treatment of cancer, with particular emphasis on breast cancer, colon cancer, prostate cancer and lung cancer - the four most common cancers in the Polish population. Material and methods: A review of the literature available on PubMed was performed using various combinations of keywords: 'polyphenols' + 'cancer', 'polyphenols' + 'oncology', ‘polyphenols’ + ‘chemoprevention’, ‘polyphenols’ + ‘chemotherapy’, 'polyphenols' + 'lung cancer', 'polyphenols' + 'breast cancer', ‘polyphenols’ + ‘colorectal cancer’, 'polyphenols' + 'prostate cancer'/'prostate gland cancer'. Results: The analysis of the collected publications allows to conclude that polyphenols exert multidirectional anticancer effect through antioxidant, antiproliferative, anti-inflammatory, immunomodulatory and prosenescence activity. This effect has been demonstrated, among others, in relation to cellular models of colorectal cancer, prostate cancer, breast cancer, cervical cancer and lung cancer. Polyphenols also reduce side effects associated with the use of conventional anticancer therapies and increase their effectiveness. Conclusions: Polyphenols - both as independent compounds and components of complex anticancer treatment regimens - have chemopreventive and potentially chemotherapeutic effects. By influencing various stages of carcinogenesis - initiation, promotion and progression of cancer - they constitute a promising direction for the development of new, more effective forms of therapy and prevention of cancer.